An Evaluation of Instructional Management for Developing Social Engineering Skills through the Social Engineering Process among Thai Language Major Students, Faculty of Education, Lampang Rajabhat University - Chayaowsakoon, Piboon; Wanitpiput , Isariyaporn; Upasod , Anan (Dhammathas Academic Journal, 2026)
The objectives of this research were: 1) to study the factors related to learning management for developing social engineering skills through the Social Engineering Process among Thai Language Program students, Faculty of Education, Lampang Rajabhat University; and 2) to assess the social engineering skills of these students.The study employed a Mixed Methods Research design. The population consisted of 30 Thai Language Program students at the Faculty of Education, Lampang Rajabhat University, during the 2024 academic year, selected through purposive sampling. The research instruments included a questionnaire and an interview form. Quantitative data were analyzed using mean, standard deviation, t-test and content analysis. The findings revealed that: 1. The study findings revealed that the factors related to the learning management for social engineer skill development, ranked from the highest to the lowest mean scores, were as follows: student characteristics, budget for activity implementation, training management process, and activity venue, with mean scores of 3.96, 3.89, 3.88, and 3.86, respectively. 2. The assessment of social engineering skills before and after the activities using the Paired-sample t-test showed that the critical t-value (df = 29, α = 0.05) was 2.045, while the calculated t-value was 16.91 This indicates that the learning management process significantly developed the students’ social engineering skills at the 0.05 level of statistical significance.